2018
DOI: 10.1002/hpm.2552
|View full text |Cite
|
Sign up to set email alerts
|

A random forest and simulation approach for scheduling operation rooms: Elective surgery cancelation in a Chinese hospital urology department

Abstract: Many hospitals encounter surgery cancelations for various reasons. We present a methodology applying data mining and simulation to optimize operating room (OR) scheduling in a urology department in West China Hospital. To the best of our knowledge, this is 1 of the first efforts to seek an optimal schedule solution based on cancelation risk of elective surgeries as well as OR allocation between elective and nonelective surgeries. First, chi-square test and random forest prediction modeling were used to predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…Generally, patient's age and medical cost present a relationship of smile curve which means that higher or lower the patient's age is, the higher the medical cost is, for the relatively poor immunity of the elderly and children, and their greater difficulty to recover from the disease, prolonging the treatment time and LOS inevitably 14,21 . However, in terms of stroke, results in our study indicate that apart from adolescent group whose age were under 20 years old, with the increasing of age, the hospitalization costs of patients in other age groups decreasing relatively, but the risk of in‐hospital death increasing accordingly.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Generally, patient's age and medical cost present a relationship of smile curve which means that higher or lower the patient's age is, the higher the medical cost is, for the relatively poor immunity of the elderly and children, and their greater difficulty to recover from the disease, prolonging the treatment time and LOS inevitably 14,21 . However, in terms of stroke, results in our study indicate that apart from adolescent group whose age were under 20 years old, with the increasing of age, the hospitalization costs of patients in other age groups decreasing relatively, but the risk of in‐hospital death increasing accordingly.…”
Section: Discussionmentioning
confidence: 66%
“…In addition to LRs (linear regression and logistic regression) methods, data mining methods 13 have been broadly employed in the literature of health care researches, such as random forest (RF), 14 gradient boosting decision tree (GBDT) 15 and artificial neural network (ANN) 16 . RF and GBDT are advanced rule‐based approaches which ensemble learning methods by developing a large number of decision trees either in parallel or serial fashion 17 .…”
Section: Methodsmentioning
confidence: 99%
“…Out of the reviewed papers, about 66% incorporate some sort of variability and the surgery duration uncertainty is most frequently taken into account in both settings. [4, 5, 7, 9, 11, 12, 14, 16, 19, 24, 28, 35, 40, 42, 47, 48, 51, 78, 87, 89, 98, 99, 102, 107, 111, 123, 126-128, 135, 142-144, 152, 156, 159, 164, 166, 171, 172, 181, 186, 187, 189, 191, 193, 199, 200] [ 4, 5, 12, 16, 19, 24, 29, 35, 44, 45, 47, 58, 65, 72, 78, 79, 87, 94, 111, 115, 123, 126-128, 135, 138, 143, 144, 152, 156, 189, 191, 195, 200, 210] Demand 33% (51/30) [2, 13, 15, 21, 22, 25-27, 30, 36, 38, 43, 50, 52, 53, 63, 68, 70, 74, 80, 86, 88, 101, 103, 105, 106, 109, 117-121, 130, 134, 147, 148, 154, 161, 162, 169, 177, 179, 183, 185, 188, 190, 192, 201-203, 212] [ 15,22,33,34,36,38,39,43,50,63,68,70,86,103,109,117,119,120,149,151,161,169,170,177,185,190,192,196,201,202] Duration 54% (79/54) [3, 6, 8, 13, 15, 18, 20, 22, 23, 26, 27, 30, 36, 38, 41, 43, 49, 53, 55, 63, 68, 69, 74, 80, 86, 88, 90, 100, 101, 105, 106, 109, 112-114, 117, 119-122, 124,...…”
Section: Activity Uncertainty and Modeling Assumptionsmentioning
confidence: 99%
“…Unplanned surgery cancellation (USC) is a widespread problem for many health care organizations, [16][17][18][19][20] which causes distress and inconvenience to patients, affects health care quality, wastes operating room resource, and leads to low operational inefficiency. Many studies reported that the incidence of USC was higher than 10%, even more than 40% in Low-and middle-income countries.…”
Section: Research-article2020mentioning
confidence: 99%